IoT Microcontroller Application Prototype as Data Transceiver from Network to USB Device - Rieke Wijayanti; M. Syirajuddin S; Abdul Rasyid; Ahmad Wilda Y (Jurnal RESTI (Rekayasa Sistem dan Teknologi Informasi), 2023)
Telecommunications technology in the early 2000s until now has experienced a rapid increase. Starting with complex devices to microcomputer devices that are able to connect to the network. With the development of networking technology, it will leave behind non-network-support devices that can still be used. The existence of previous research on "The interface between the IoT microcontroller (ESP32) and the Max3421e USB Host" can be taken advantage of developing a device that can facilitate a non-support-network device into a support-network electronic device. So that non-support-network electronic devices do not become electronic waste and can also become a device that can be used in the present. In this study, a prototype of a data receiver from WiFi was designed, then the data that has been received is reorganized into rows of data that are ready to be sent to non-support-network electronic devices. This developed tool uses an ESP32 IoT microcontroller connected to the USB Host max3421e which has been packaged in the form of a USB host shield module using SPI protocol communication. The result obtained is that data from the network can be sent correctly to the USB Host max3421e via the ESP32 microcontroller.